THE DEVELOPMENT OF GREEN EDUCATION-BASED DIGITAL ENGLISH STORYBOOKS FOR PRIMARY SCHOOL STUDENTS - Adinda Nazwa Kharisma; Dayu Retno Puspita; Asih Rosnaningsih (J-Shelves of Indragiri (JSI), 2026)
This study was motivated by learning boredom and difficulties in English vocabulary retention experienced by third-grade elementary school students due to reliance on conventional rote-memorization methods. The purpose of this Research and Development (R&D) study was to design, test the feasibility, and analyze the effectiveness of an instructional medium in the form of a Green Education-Based English Digital Storybook titled Learning from the Green School. The research method utilized the 4D model (Define, Design, Develop, Disseminate). The research subjects involved all 32 third-grade students at SDN Gondrong 4, Tangerang City, with the cognitive effectiveness trial focusing on 23 core subjects who had baseline learning scores below 90. Data collection instruments included expert validation questionnaires, user response questionnaires, and test instruments (pretest and posttest). The results indicated that the developed product is highly feasible for implementation based on the evaluations from the material expert (96%), language expert (94%), media expert (92%), and educational practitioner (96%). This feasibility assessment was further supported by user responses through teacher and student feedback questionnaires, which yielded a mean scoring percentage ranging from 93% to 96%, falling into the highly excellent and effective criteria. Based on the product trials, a significant increase in the students' cognitive mean scores was observed across all three trial phases: the individual trial (one-to-one) increased from 55 to 88, the small-scale trial increased from 58 to 90, and the large-scale trial increased from 60 to 92. The hypothesis testing through the Paired Samples T-Test yielded a significance value of (sig. > 0,05),meaning that H0 is rejected and Hα is accepted. Consequently, the Green Education-Based English Digital Storybook is proven to be feasible, practical, and significantly effective in improving the cognitive learning outcomes of third-grade elementary school students.